Alkali Modification and Pyrolysis of Rice Husks for Bioenergy Potential: A Kinetics Study - Vianney Andrew Yiga; Michael Lubwama; Peter Wilberforce Olupot (Energy Science & Engineering)
ABSTRACT Rice husks are significantly creating environmental challenges in terms of air pollution because of their unsustainable disposal methods. In this study, pyrolysis of sodium hydroxide (NaOH) alkali‐modified rice husks using thermogravimetric analysis (TGA) was carried out to determine combustion and kinetic parameters at three different heating rates of 20, 40, and 50°C/min for application in biofuels. Combustion performance was analyzed from the results of ignition temperature, burn‐out temperature, combustion rates, flammability index, and combustion characteristic index. The increase in heating rate from 20°C to 40°C and further to 50°C/min increased the onset of degradation, burnout, and peak temperatures as observed by curve shifts to the right. This was likely due to a shorter reaction time when a higher heating rate was utilized, increasing the temperature required for degradation. Flammability and combustion characteristic index ranged between 0.8 × 10−5–1.1 × 10−5%/min.°C2 and 0.3 × 10−8–0.4 × 10−8%/min/°C respectively, and their values decreased with increasing heating rates since it takes longer to transfer heat from the external environment to the interior of the rice husks, thereby creating a hysteresis effect. The average activation energies for modified K85 (kaiso) and modified K98 (supa) rice husks using the Kissinger–Akahira–Sunose (KAS) method were 104.5 kJ/mol and 105.4 kJ/mol as well as 109.4 kJ/mol and 110.3 kJ/mol using the Ozawa–Flynn–Wall (OFW) method. Enthalpy, Gibbs free energy, and Entropy changes were in ranges 103.9–105.0 kJ/mol, 160.8–167.5 kJ/mol, and 0.09 kJ/mol.K, respectively. The low energy barrier (≤ 7.0 kJ/mol) between activation energy and enthalpy changes indicated that modified rice husk initiation occurs easily and can easily be transformed into biofuels. In general, the findings from this work have confirmed the feasibility of modified rice husks as a potential source of bioenergy.